New species of the genus Lytocestus (Caryophyllidea lytocestidae) from catfish in Aurangabad dist (M.S.), India - Sunita Borde, *Sushil Jawale and (International Multidisciplinary Research Journal, 2011)
Two new caryophyllidean species of the genus Lytocestus from catfish Clarias batrachus (L.) from Aurangabad District is described. The differential characters of Lytocestus khami Sp. Nov. has elongated body bluntly tapering at both side, differentiated head, large saccular uterus.